IoT based patent monitoring system - Hoque, Israt Jarin; Navid, Md.Shadman; Reza, Rifat Binte; Mahbub, Mashwab Ibna (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.